Digital Technologies Formation for University Education under Covid-19 - Valery M. ABRAMOV; Evgeniy A. BAIKOV; Vladimir A. BOLSHAKOV; Vyacheslav G. BURLOV; Eugene P. ISTOMIN; Valery L. MIKHEEV; Nickolay N. POPOV; Mikhail B. SHILIN; Igor A. SIKAREV; Tatiana M. TATARNIKOVA (Communications of International Proceedings, 2021)
Paper presents results of learning digital technologies formation for university education under Covid-19. In studies, there are used methods of data bases constructing within learning digital platforms, web-technologies and virtual reality tools. While Covid-19 conditions, universities have to work on digital transformation of university education, including creation of new concepts for obtaining and presenting didactical materials, including practical works and trainings. Authors propose to use learning digital platforms, which integrate heterogeneous hardware and software resources with the use of web-technologies in distributed networks and wide application of cloud services. It is proposed to use Google Classroom, as more convenient learning digital platform among others.  Also, authors propose to use geo-information digital online platforms for educational purposes within geo-information management disciplines. There are presented the enlarged groups of didactical works in this area. Considered the issues of digital content creation at university education level, especially within practical training. While research, platform https://www.researchgate.net/profile/Valery_Abramov2/ was used for data exchange and preliminary discussion.
Keywords: learning digital technologies; university education; practical training; Covid-19